Answer:
x + y = -1
Explanation:
To write the equation of a line, find the slope and use it with a point in the point slope form.
You can find the slope using the slope formula.
![m = (y_2-y_1)/(x_2-x_1) = (5--3)/(-6-2) = (8)/(-8)=-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dplrmj4dq7nvxpl4i9kejyikzlsp72f87c.png)
Substitute m = -1 and the point (2,-3) into the point slope form.
![y - y_1 = m(x-x_1)\\y --3 = -1(x-2)\\y+3=-1(x-2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3qmhvdajluupzf79gk199hjgltitxcw9wg.png)
Convert to standard form by applying the distributive property and rearranging the terms.
y+3 = -1(x-2)
y + 3 = -x + 2
x + y + 3 = 2
x + y = -1